Towards a cross platform solution to share small-scale data across smart devices using visible light: a prototype developed in android environment - Fairooz, Faizah; Chowdhury, Prothoma; Ahmed, Rezwana (BRAC Univeristy, 2018)
This thesis report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2016.